Who speaks for climate migrants? A justice-oriented bibliometric analysis of Global South research - Aziz, Mudassar; Anjum, Gulnaz; Nawaz, Abdul Rehman; Nadeem, Imran (Frontiers in Climate, 2025)
This study presents a comprehensive bibliometric analysis of climate-induced migration research in the Global South (2000–2024), critically examined through the lens of climate justice. Drawing on 204 peer-reviewed publications from Scopus and Web of Science, the analysis maps scholarly production, citation patterns, thematic evolution, and global collaboration networks using Biblioshiny and VOSviewer. Results reveal a significant surge in research post-2015, with intellectual roots grounded in environmental migration, but shifting progressively toward integrated themes of climate justice, human rights, adaptation, and vulnerability. High-impact contributions remain concentrated among Global North institutions, particularly the United States, United Kingdom, and Australia, although authorships are increasingly diversifying to include regions such as South Asia, Sub-Saharan Africa, and Small Island Developing States. Thematic mapping shows a maturing field marked by convergence of legal, political, ecological, and social science perspectives. However, critical gaps persist including limited attention to under-researched geographies, destination outcomes, gendered and intersectional experiences, and understanding trapped populations and immobility. South–South collaborations remain marginal, and dominant framings often reproduce epistemic hierarchies that overlook local agency and decolonial critiques. The study identifies urgent directions for future research, including deeper interdisciplinary integration, participatory and context-sensitive methodologies, and the application of attribution science to quantify climate-related displacement. By centering equity, representation, and the differentiated impacts of climate stress, this bibliometric perspective contributes not only to mapping the landscape of climate migration scholarship but also to advancing a justice-oriented research agenda. It calls for a paradigm shift where migration is understood not merely as a risk, but as a space for resilience, rights, and transformation, particularly for the most vulnerable in the Global South.